Exploring the Dimensions of Marital Satisfaction among Married Teachers in Kwara State: Implications for Counsellors and Educators - Jamila YUSUF; Habibat Bolanle ABDULKAREEM (Jurnal Pendidikan Ilmu Sosial, 2024)
Marital contentment holds paramount importance for individuals' overall welfare, especially among professionals such as teachers facing distinctive daily pressures. This paper conducts a thorough analysis of the diverse factors influencing marital satisfaction among teachers in Kwara State, Nigeria, drawing insights from existing literature. It delves into various facets including personal fulfillment, emotional health, individual development, communication, intimacy, and interpersonal dynamics like mutual comprehension and conflict resolution. By integrating cultural, religious, and psychological viewpoints, the review underscores the crucial role of marital satisfaction in fostering societal cohesion and personal gratification. Moreover, it outlines implications for counseling and education, stressing the necessity of a holistic approach in supporting teachers' marital welfare. The paper concludes with the following suggestions  There should be collaborative efforts between various stakeholders such as marriage counselors, educational institutions, governmental bodies, religious institutions, and NGOs are to organize educational seminars and workshops in other to educate both prospective couples and married individuals about nurturing a happy and peaceful home environment.Counsellors should advocate for teachers to develop effective problem-solving skills inorder to navigate challenges and improve marital satisfaction.Collaborative Conflict Resolution should be encouraged among counsellors and teachers to resolve conflicts among married secondary school teachers, as it has shown efficacy in fostering satisfactory marriages. However, this would enable stakeholders to cultivate an enabling environment conducive to nurturing joyful and fulfilling marriages among married teachers in Kwara State.